Asuhan Kebidanan Komprehensif pada Ny. P dengan Anemia Ringan dan By. Ny. P dengan Asfiksia Neonatorum Sedang di Kota Pontianak - Sofia Afritasari; Nurhasanah Nurhasanah; Nur Safika (Pusat Riset dan Inovasi Nasional, 2025)
Comprehensive midwifery care is a service provided by midwives during pregnancy, childbirth, BBL, postpartum period and family planning program which aims to provide quality services to prevent maternal and child mortality. Research Objective : This study aims to provide comprehensive midwifery care to Mrs. P who has mild anemia and By. Mrs. P with moderate asphyxia. Research Method: This case uses an approach method to study comprehensive midwifery care for Mrs. P and By. Mrs. P in Pontianak City. Research Results: After providing care for 9 months starting from Pregnancy, Childbirth, Postpartum, Infants and Toddlers, Family Planning and Immunization. The results were normal pregnancy, normal childbirth, postpartum, newborns with moderate neonatal asphyxia, family planning using pills, Hepatitis-B immunization to measles. Conclusion: In the midwifery care provided to Mrs. P and By. Mrs. P at PKM Pontianak City, there were differences between theory and management.